2021
DOI: 10.4000/rfst.1210
|View full text |Cite
|
Sign up to set email alerts
|

Portrait de donneurs de sang à Montréal (Canada) : typologie en fonction de leurs déplacements quotidiens

Abstract: Référence électronique Marie-Soleil Cloutier, Élianne Carrier et Johanne Charbonneau, « Portrait de donneurs de sang à Montréal (Canada) : typologie en fonction de leurs déplacements quotidiens », Revue francophone sur la santé et les territoires [En ligne], Miscellanées, mis en ligne le 16 juin 2021, consulté le 16 juin 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…Petrovay (1990) could also demonstrate that the morphology of convection can then be predicted. Extending the nonlocal MLT formalism of Shaviv and Salpeter (1973), Cloutier (2018) further showed that assuming the thermodynamic quantities vary linearly with depth, local MLT is retrieved but with a nonzero kinetic energy flux of a form similar to that found in Chan and Sofia (1989). Another caveat of local MLT that is fixed with a nonlocal formalism, is the absence of convective overshooting beyond the Schwarzschild barrier, as convective elements reach it with a finite velocity and need a finite time to deccelerate.…”
Section: Mean-field Hydrodynamics and Mixing-length Theorymentioning
confidence: 83%
“…Petrovay (1990) could also demonstrate that the morphology of convection can then be predicted. Extending the nonlocal MLT formalism of Shaviv and Salpeter (1973), Cloutier (2018) further showed that assuming the thermodynamic quantities vary linearly with depth, local MLT is retrieved but with a nonzero kinetic energy flux of a form similar to that found in Chan and Sofia (1989). Another caveat of local MLT that is fixed with a nonlocal formalism, is the absence of convective overshooting beyond the Schwarzschild barrier, as convective elements reach it with a finite velocity and need a finite time to deccelerate.…”
Section: Mean-field Hydrodynamics and Mixing-length Theorymentioning
confidence: 83%